Peran Strategi Pengelolaan Manajemen pada Hubungan Modal Intelektual dan Kinerja Perusahaan - Aryanindita, Gabriel P; Tarigan, Thia Margaretha; Nugroho, Felix Cahyo (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2024)
The advent of information technology has precipitated a paradigm shift in the global business landscape. One of the principal factors contributing to the ability of organisations to adapt to this paradigm shift is the capacity of their employees. Intellectual capital has emerged as a new area of focus in accounting research. There is a substantial body of empirical evidence that attests to the significance of intellectual capital enhancement for business strategy. Nevertheless, there is a paucity of empirical research examining the relationship between knowledge management strategies and intellectual capital and organisational performance. The objective of this study is to make a contribution to the empirical investigation of knowledge management strategy, specifically in relation to 556 companies from the Southeast Asia region for the period 2021-2023, as identified from the I/B/E/S database. The results of the study indicate that there is no significant effect of value-added intellectual coefficient (VAIC), which represents a firm's intellectual capital, on performance (return on investment (ROI)). This is due to the lack of complete data for calculating VAIC. Employee costs are the primary account used to calculate VAIC, and thus, knowledge management strategies may be perceived as less critical by managers when intellectual capital is not a primary concern.